First record of a deep-sea tardigrade from the South China Sea, Halechiniscus janus sp. nov. (Arthrotardigrada: Halechiniscidae) - Bai, Lifen; Wang, Xiaogu; Gao, Xiaohui; Li, Yujie; Fontoura, Paulo (Zootaxa, 2022)
The knowledge of marine tardigrades in the South China Sea (Western Pacific Ocean) is very scarce, with only four species from shallow waters recorded until now. The first deep-sea (1530–1624 m bsl) tardigrade species from this sea, Halechiniscus janus sp. nov. (Arthrotardigrada: Halechiniscidae), is described here. Specimens of the new species have four wrinkled digits without peduncles on each leg, terminated by simple crescent-shaped claws, and primary clavae clearly shorter than cirri A, both inserted on a common cirrophore, as typical for the genus Halechiniscus Richters, 1908. The new species differs from all other Halechiniscus species by its cylindrical body and conical head; by the presence of semispherical secondary clavae, and by sensory organs on legs IV consisting of a short cirrophore followed by a short papilla terminated in a peculiar short bipartite tip. The discovery of this new bathyal species, with its peculiar morphological traits, brings new insights not only to the biogeography and ecology of tardigrades, but also to the understanding of the only partially resolved systematics of the diversified family Halechiniscidae.